Pengaruh Customer Relationship Management, Kualitas Pelayanan, dan Kepercayaan terhadap Loyalitas Nasabah Pembiayaan BSI OTO pada Bank Syariah Indonesia KCP Nganjuk Yos Sudarso - Pratama, Riyan Anang (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2025)
Islamic banks in Indonesia, including in Nganjuk, offer financing products based on sharia principles to meet the needs of the community, such as BSI OTO, which facilitates the purchase of vehicles with schemes in accordance with Islamic values. BSI OTO is a sharia automotive financing service resulting from a collaboration between Bank Syariah Indonesia and PT Mandiri Utama Finance Unit Usaha Syariah. BSI OTO offers low margins, easy installments, fast applications, and a variety of vehicle options, as well as guaranteeing sharia principles without usury, gharar, and maisir. This study aims to analyze the effect of customer relationship management (CRM), service quality, and trust on customer loyalty of BSI OTO financing at Bank Syariah Indonesia KCP Nganjuk Yos Sudarso, both partially and simultaneously. This study uses a quantitative method with incidental sampling techniques. A total of 100 questionnaires were distributed to BSI OTO customers. The independent variables include CRM, service quality, and trust, while the dependent variable is customer loyalty. Data were analyzed using classical assumption tests, multiple linear regression, and hypothesis testing. The results show that service quality has a significant influence on customer loyalty, while CRM and trust do not have a significant influence. However, simultaneously, all three variables have an effect on customer loyalty with an R square of 0.284, or 28.4%. This study provides insight into the factors that influence customer loyalty to sharia financing products in Indonesia, especially BSI OTO, and underlines the importance of service quality in increasing loyalty. Keywords: Customer Relationship Management (CRM), Service Quality, Trust, Loyalty